Analisis Perilaku Konsumen Dalam Pembelian Buah Lokal Di Pasar Tradisional Arengka Kota Pekanbaru - Tarigan, Abdul Rahman; Hadi, Syaiful; Sayamar, Eri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to analyze the attitude, subjective norm and consumer behavior towards buying local fruit. This research was conducted in traditional market Arengka Pekanbaru. Source of data was primary data from interview with respondents using accidental random sampling. Methods of analysis is Fishbein formula to show consumers attitude to certain object and to know consumers decision making process. The results showed that the attitude of consumers in buying local fruit is good. Subjective norm consumers indicate referent not affect consumers in buying local fruit. The consumers behavior in buying local fruit showed a significant positive result is good. Keywords : Attitude, Subjective Norm, Consumer Behavior